Prevalence of Antenatal Mental Health Problems of Pregnant Women Living in Thai Myanmar Border Area, Umphang Hospital, Thailand - Walairat Kemthong (The Royal Thai College of Obstetricians and Gynaecologists, 2011)
Objective: To determine the prevalence and risk factors associated with mental health problems in pregnant women. Material and Method: The 245 singleton pregnant women with no previous history of psychiatric illness were asked to complete a Thai General Health Questionnaire (GHQ-12) (mental health screening tool) at Umphang hospital(a primary hospital). The prevalence of mental health problems and associated risk factors were determined.Results: The prevalence of mental health problems in this study was 24.5%. The risk factors of mental health problems in this study were history of abortion, non-Thai speaking, smoking, severe vomiting and vaginal bleeding during pregnancy. Conclusion: The prevalence of mental health problems in pregnant women was high. Pregnant women should be screen for mental health problems particularly in the high risk group.